2018
DOI: 10.5195/ie.2018.80
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning the Education Doctorate for Community College Leaders: Generation, Transformation, and Use of Professional Knowledge and Practice

Abstract: This paper describes the redesign of a community college executive leadership doctoral program that seeks to develop senior-level leaders.  The paper provides how the redesign was intentionally aligned with the CPED principles and specifically the sixth principle. The paper sought data from students, faculty and other documents to gain an insight into the impact of aligning the program with principles and design concepts.  The paper suggests that it is important for this program to integrate examples from prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Zambo et al (2014) similarly reported how their higher education program students viewed programs as meaningful for their career mobility. Meanwhile, Bartlett et al (2018) described relevant learning activities as a necessary component for community college leadership preparation programs. Over the decades, authors exploring these trends have arrived at similar conclusions: students seek programs that authentically present real-life problems they can solve and apply to their professional leadership roles (Dressel & Mayhew, 1974;Nelson, 1987;Townsend, 1990).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Zambo et al (2014) similarly reported how their higher education program students viewed programs as meaningful for their career mobility. Meanwhile, Bartlett et al (2018) described relevant learning activities as a necessary component for community college leadership preparation programs. Over the decades, authors exploring these trends have arrived at similar conclusions: students seek programs that authentically present real-life problems they can solve and apply to their professional leadership roles (Dressel & Mayhew, 1974;Nelson, 1987;Townsend, 1990).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our study follows these four constructs, as students participate in applied doctoral programs, typically enrolling on a part-time basis and in cohorts where they must engage with and process problems that can shape their practice. Leadership preparation programs provide a foundation of theoretical familiarity and present opportunities for students to identify alignment between research and practice (Bartlett et al, 2018;Townsend, 1990). Understanding how doctoral community college leadership programs enable students to address educational issues with real-world implications can unravel how action learning manifests in curricular and co-curricular experiences.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The CCL program at North Carolina State University has recently been redesigned to align better with the CPED principles (Bartlett et al, 2018). The EdD program redesign efforts have been supported in part by a grant from a funder to provide resources to enhance the doctoral students' experience.…”
Section: Context Of CCL Edd Programmentioning
confidence: 99%
“…Untuk memastikan program tetap berpusat pada siswa dan terus meningkat, penilaian yang disengaja diintegrasikan di seluruh program untuk mengumpulkan perspektif mahasiswa dan fakultas dan bahwa informasi tersebut digunakan untuk penyempurnaan program. Salah satu contoh adalah persepsi siswa tentang keberhasilan mahasiswa perguruan tinggi (Bartlett, Bartlett, Dolfi, Jaeger & Chapman, 2018 (Azmi, Kitan, Noordin, & Nasir, 2018).…”
Section: Pembahasanunclassified